Between Legality and Morality: The History of Gambling in Semarang City in 1970-1993 - Rahmawati, Diah Novia Ari; Wijayati, Putri Agus (JUSPI (Jurnal Sejarah Peradaban Islam), 2025)
This study explores the process of gambling legalization in the city of Semarang during the period from 1970 to 1993. The background of the research lies in the contradiction between the moral and legal prohibition of gambling and the reality of government policies that legalized such practices in the form of prize lotteries. The aim of this study is to understand the socio-political dynamics behind the legalization of gambling and its impact on urban society in Semarang. The research adopts a historical method, which includes the stages of heuristics, source criticism, interpretation, and historiography. Primary sources consist of local newspapers and legislative regulations. The findings reveal that the legalization of gambling was a state strategy to raise public funds for development while simultaneously attempting to control illegal gambling activities. On the other hand, the policy also illustrates how the state compromised social norms in pursuit of economic interests and political stability. The conclusion of this study is that the legalization of gambling in Semarang was not merely a response to fiscal needs, but also a reflection of the power relations between the state and society during the new order era.